New Dimensions in Community Well-Being - Kraeger, Patsy; Cloutier, Scott; Talmage, Craig (Springer International Publishing : Imprint: Springer, 2017)
This volume addresses new innovations in quality of life and well-being from the perspectives of the individual, society and community. It aggregates the perspectives, research questions, methods and results that consider how quality of life is influenced in our modern society. Chapters in this volume present theoretical and practical examples on different aspects of quality of life and community well-being representing American, European, Native American and African perspectives. This volume is of interest to scholars in sociology, psychology, economy, philosophy, health research as well as practitioners across the social sciences. .
Keywords: Social sciences.; Medical research.; Social structure.; Social inequality.; Quality of life.; Emigration and immigration.; Community psychology.; Environmental psychology.; Positive psychology.; elektronické knihy; electronic books